Sulfonic Group Functionalized Periodic Mesoporous Ethylenesilica: A Highly Efficient and Reusable Catalysts for Carbon‐Carbon Coupling Reaction. Issue 1 (7th December 2018) - Zhang, Linlong; Zhou, Wei; Xu, Yong; Wang, Yaoyao; Hu, Jianglei; Shi, Fengwei
Abstract: One‐pot method for the preparation of well‐ordered periodic mesoporous ethylenesilica functionalized in‐situ with sulfonic groups ( pr ‐SO3 H‐PMO) was deployed successfully. The sulfonic groups have been used as a Brønsted acid to catalyze the carbon‐carbon coupling reaction of α‐electron‐withdrawing group (EWG) ketene dithioacetal derivatives and benzhydrol. Meanwhile, this series of materials exhibit excellent catalytic performance in the C−C coupling reaction and pr ‐SO3 H‐PMO(0.39) possesses highly efficient catalytic performance among the prepared materials, over which the conversion of ketene dithioacetals achieved 98.3% and the yield of the coupling products reached 93.4%. In addition, evidence is presented that the catalytic activity of pr ‐SO3 H‐PMO(0.39) material has been recycled up to five times without a significant reduction. Abstract : Heterogeneous mesoporous catalysts pr ‐SO3 H‐PMO containing different amounts of propylsulfonic groups have been successfully synthesized. The materials possessed highly ordered mesostructures. Catalytic tests showed that the heterogeneous mesoporous catalysts pr ‐SO3 H‐PMO exhibited excellent catalytic performance in carbon‐carbon coupling of α‐EWG ketene dithioacetal derivatives and benzhydrol.